A tailored graft-type polymer as a dopant-free hole transport material in indoor perovskite photovoltaics. Issue 27 (30th June 2021) - Opoku, Henry; Kim, Yun Hoo; Lee, Ji Hyeon; Ahn, Hyungju; Lee, Jae-Joon; Baek, Se-Woong; Jo, Jea Woong
Abstract : A new graft-type polymer which exhibits dual functionality of efficient charge transport and interfacial passivation was synthesized as a dopant-free hole transport material for indoor perovskite photovoltaics. Abstract : As an essential component in efficient perovskite photovoltaics (PPVs), hole transport materials (HTMs) that meet the intricate requirements for next-generation charge transport layers have recently been of immense interest. Specifically, functionally tailored HTMs that aid in mitigating charge transport limitations and interfacial defects and thereby enhance the performance of both indoor and outdoor PPVs are being sought after. Herein, we developed a novel graft-type polymer composed of a benzo[1, 2- b :4, 5: b ′]dithiophene-based main chain and poly(ethylene glycol) (PEG) side chains as an efficient dopant-free HTM for PPVs. Through a systemized tailoring of the contents of the side chains, we were able to control the hole transport and interfacial passivation abilities of the graft-type polymeric HTM. The polymeric HTM with an optimized PEG side chain exhibited a higher hole mobility, a reduced amount of interfacial traps, and an enhanced device stability compared to the control polymeric HTM. The PPVs capped with the optimized graft-type polymeric HTM demonstrated remarkably high power conversion efficiencies up to 38.2% and 21.7% under 1000 lux LED and AM 1.5 solar illuminations, respectively.